Dust Properties around the Dust Cloud nearby White Dwarf LAWD 84 in IRIS and AKARI Data (Journal of Nepal Physical Society, 2023)
An isolated dust cloud is discovered nearby the White Dwarf LAWD 84, located at (RA, DEC) (J2000): 21h19m36.53s, -55°50'4.47'', in the infrared data of Improved Reprocessingof the IRAS (IRIS) and AKARI infrared survey, within angular size 1.0° ×1.0°. The isolated region of dust cloud is found to be broken into the two parts both in IRIS and AKARI data, named as IRIS-UP, IRIS-LOW, AKARI-UP and AKARI-LOW. The isolated region of flux at 100 μm in IRIS and 140 μm in AKARI is also studied separately. The dust color temperature (Td) and dust mass (Md) are calculated from the infrared flux in both data. The average Td is found to be ∼24 K in IRIS data and ∼20 K in AKARI data in both parts. The ratio of dust mass in total region to isolated region is found ∼ 2.0 in IRIS-UP and AKARI-UP but the ratio is 5.06 in IRIS-LOW and 3.19 in AKARI-LOW clouds. The regression analysis between the infrared fluxes at two wavelength shows a linear relation between the infrared fluxes in both clouds, whereas there is no any preferred relation observed between the infrared flux (both wavelength) and dust color temperature but a direct linear relationship between infrared flux and dust color temperature, and inverse parabolic relationship obtained between the dust color temperature and dust mass in all clouds. The qualitative analysis of contour map of infrared flux, temperature and mass supports this result. Furthermore, the inclination angle of the each clouds,  background point sources, Jeans Criteria and Gaussian distribution of the dust color temperature are studied within both clouds to explain the possible ongoing physical phenomenon within the clouds.